Patient and parent knowledge, understanding, and concerns after a new diagnosis of Ehlers Danlos syndrome - Jordan T. Jones; Lora L. Black; William R. Black (Orphanet Journal of Rare Diseases)
Abstract Introduction After diagnosis of Ehlers Danlos Syndrome (EDS), it is unclear what information patients and parents need and understand about EDS. The objective of this study is to characterize patient and parent knowledge and concerns about EDS after a diagnosis of EDS is made to determine patient and parent concerns and identify barriers that cause discomfort with the diagnosis.6 Methods A convenience sample of patient and parent dyads were recruited after new diagnosis of EDS. Patients and parents completed questionnaires that assessed knowledge, comfort, and barriers of EDS before and after diagnosis, EDS education materials accessed, and additional clinical needs and concerns. Results Seventy-two dyads completed the survey. Conclusion Many respondents actively seek information on the diagnosis and management of EDS. Parents and patients look for information about EDS differently. Parents have more concerns after diagnosis and both want well-constructed, empirically supported educational materials delivered via multiple modalities, which makes clinical guidelines more essential.